Psychological aspects of caregivers associated with family support in the therapeutic adherence of diabetic patients - Miriam Teresa Domínguez - Guedea; Eva Moncada García; María Elena Reguera Torres; Paulina Márquez-Ulloa; Francisco Grijalva Fernández (Universidade de Fortaleza, 2010)
Objective: To analyze the relationship of psychological aspects of family caregivers with the support that they offer to the diabetic patient's adherence to treatment. The psychological aspects were: subjective well-being, attachment styles, coping strategies to problems and perceived social support. Methods: Joined in the study 29 family caregivers in a noneprobabilistic sample. Participants were contacted from three Mutual Aid Groups for diabetic and hypertensive patients in the city of Hermosillo, México. Questionnaires designed for the purposes of research were applied, as well as psychometric instruments previously validated in the cultural reference group. Results: The data showed that the psychological aspects that are statistically significant and negatively related to adherence therapy are avoidant attachment and negative affection, both associated to each other in a positive way, indicating that they occur in parallel. Avoidant attachment was positively associated with avoidant coping strategies and emotional disturbance, but negatively with secure attachment and material satisfaction. Negative affection were positively associated with emotional coping, but negatively with secure attachment and material satisfaction. Negative affect were positively associated with emotional confrontation, but negatively with positive affection, material satisfaction, emotional support and guidance support. Conclusions: More applied research in needed on the influence of family factors in achieving adherence to treatment, because so far, most work focuses more on the individual patient, disregarding the family factor.